3-Dimensional heat transfer modeling for laser powder-bed fusion additive manufacturing with volumetric heat sources based on varied thermal conductivity and absorptivity. (January 2019) - Zhang, Zhidong; Huang, Yuze; Rani Kasinathan, Adhitan; Imani Shahabad, Shahriar; Ali, Usman; Mahmoodkhani, Yahya; Toyserkani, Ehsan
Highlights: Eight 3D heat sources used for simulating Laser Powder-Bed Fusion are compared. New equations for varied thermal conductivity and laser absorptivity is proposed. The varied thermal conductivity and absorptivity expressions can be linear functions. Abstract: In this article, a 3-dimensional heat-transfer finite element model for Laser Powder-Bed Fusion (LPBF) was developed for accurately predicting melt pool dimensions and surface features. The sole deployment of trial-and-error experiments for arriving at optimal process parameters is very costly and time-consuming, thus the developed model can be used to reduce the process/material development costs. A literature review of heat source models was presented. Eight commonly used heat source models are evaluated and compared. All of their simulated depths are smaller than the experimental result, which may be due to the melt pool convection and inconstant laser absorptivity in the reality during the experiment. In order to enable the numerical model to predict melt pool dimensions for different combinations of process parameters, a novel model including expressions of varied anisotropically enhanced thermal conductivity and varied laser absorptivity is proposed and verified by both the melt pool dimensions and track surface morphology. It is found that the heat source expressions can be linear while causing the simulation results to be in better agreement with both experimental melt pool dimensions and track surface morphology.